2009
DOI: 10.1111/j.1471-0528.2009.02322.x
|View full text |Cite
|
Sign up to set email alerts
|

Soy intake and risk of endocrine‐related gynaecological cancer: a meta‐analysis

Abstract: Background Epidemiology studies have reported associations between soy intake and the risk of endocrine-related gynaecological cancers. However, to date there have been no quantitative meta-analyses reported regarding this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 48 publications
1
46
0
3
Order By: Relevance
“…In particular, the polyphenols epicatechin gallate and EGCG in green tea appear to have significant anticancer effects (38,197,283). Intake of soy, an important source of the isoflavone genistein, has been associated with up to 49% reduced risk of endometrial and ovarian cancers in women (182). Epidemiologic studies of cocoa intake and cancer risk are few, and those assessing overall mortality provide only a FPWA increased to a greater extent in older subjects.…”
Section: Effects On Immune Function and Carcinogenesismentioning
confidence: 99%
“…In particular, the polyphenols epicatechin gallate and EGCG in green tea appear to have significant anticancer effects (38,197,283). Intake of soy, an important source of the isoflavone genistein, has been associated with up to 49% reduced risk of endometrial and ovarian cancers in women (182). Epidemiologic studies of cocoa intake and cancer risk are few, and those assessing overall mortality provide only a FPWA increased to a greater extent in older subjects.…”
Section: Effects On Immune Function and Carcinogenesismentioning
confidence: 99%
“…Genistein is a soy-derived isoflavone and has shown protective effects against endocrine-related gynecological cancers [41,68]. A meta-analysis study demonstrated an inverse correlation between soy intake and ovarian cancer risk.…”
Section: Genisteinmentioning
confidence: 99%
“…Results from a meta-analysis showed that high intake of isoflavonoids or soy-based food were associated with a decreased risk of ovarian cancer (4). Half of these studies were conducted in an Asian population were the intake of soy products are much higher than in a Western population.…”
Section: Introductionmentioning
confidence: 99%